China's new art, post 1989 (Hanart TZ Gallery, 1993)
China's New Art, Post-1989 was the first major collection of Chinese experimental art to exhibit outside the country. The exhibition took place between January 30 to February 28, 1993, as part of Hong Kong Arts Festival in Hong Kong City Hall and at Pao Galleries, Hong Kong Arts Centre. The touring exhibition travelled to Taipei, Melbourne, London, Vancouver, and various cities in the USA from 1993 to 1997. Considered a seminal snapshot of the Chinese avant-garde scene of the time, the exhibition served as an inspiration[1] for the exhibition "Art and China after 1989: Theatre of the World" presented in 2017 at the Guggenheim Museum in New York. Painting, Political Pop, Cynical Realism, performance art, abstraction, installation, calligraphy, China, group exhibition
English; Chinese
Keywords: 21st century; Contemporary Art; N5300-7418 Visual Arts- History; China